2011
DOI: 10.1007/s12035-011-8192-2
|View full text |Cite
|
Sign up to set email alerts
|

The Mitochondrial Aspartate/Glutamate Carrier AGC1 and Calcium Homeostasis: Physiological Links and Abnormalities in Autism

Abstract: Autism spectrum disorder (ASD) is a severe, complex neurodevelopmental disorder characterized by impairments in reciprocal social interaction and communication, and restricted and stereotyped patterns of interests and behaviors. Recent evidence has unveiled an important role for calcium (Ca(2+)) signaling in the pathogenesis of ASD. Post-mortem studies of autistic brains have pointed toward abnormalities in mitochondrial function as possible downstream consequences of altered Ca(2+) signaling, abnormal synapse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 91 publications
2
38
0
1
Order By: Relevance
“…Mutations in the aspartate/glutamate mitochondrial transporter, SLC25A12, have been previously associated with ASD [47]. This transporter is an important component of the malate/aspartate shuttle, a crucial system supporting oxidative phosphorylation, adenosine triphosphate production, and key metabolites for the urea cycle [47].…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the aspartate/glutamate mitochondrial transporter, SLC25A12, have been previously associated with ASD [47]. This transporter is an important component of the malate/aspartate shuttle, a crucial system supporting oxidative phosphorylation, adenosine triphosphate production, and key metabolites for the urea cycle [47].…”
Section: Discussionmentioning
confidence: 99%
“…In 2004 (102)(103)(104). In contrast, they detected hints of an abnormal functioning of mitochondria due to a permanent activation by excessive elevated Ca 2þ levels.…”
Section: Aralar and Diseasesmentioning
confidence: 98%
“…In contrast, they detected hints of an abnormal functioning of mitochondria due to a permanent activation by excessive elevated Ca 2þ levels. This led them to the conclusion that mutations in other proteins are probably responsible for the primary Ca 2þ -related dysfunctions resulting in permanently increased Ca 2þ cyt and this secondarily causes a permanent over-energization of mitochondria (102).…”
Section: Aralar and Diseasesmentioning
confidence: 99%
“…Furthermore, the maintenance of calcium homeostasis is crucially important in the functioning of immune cells, 3 and recent studies have revealed evidence of altered Ca 2? homeostasis in ASD (Palmieri et al 2008;Napolioni et al 2011). Together, these studies point towards a causal link from channel-mediated intracellular calcium imbalance in autism and the disturbed neurodevelopment of autistic subjects.…”
Section: Model Of Channelopathymentioning
confidence: 99%
“…Dysregulated calcium homeostasis has been observed at the macro level by Palmieri et al (2008). This finding of dysregulated homeostasis was later linked with calcium signalling defects by Napolioni et al (2011). It is known that voltage-gated calcium channels are essential to neuronal maturation and differentiation, in addition to their central function in neural information processing (McEnery et al 1998).…”
Section: Model Of Channelopathymentioning
confidence: 99%